Optimisation method of extrusion dies with a thin and complex shape - Kathirgamanathan, P.; Neitzert, T. (Taylor & Francis Group, 2014)
Extrusion dies are usually manufactured with a rectangular pocket in front of the actual die opening. Finite element simulations demonstrate that curved or slant shaped pockets can assist in a more homogenous material flow in terms of velocity and shear stresses. An efficient optimisation algorithm has been developed for different pocket widths of slant die pockets. The algorithm incorporates finite element simulations to predict improvements in material flow. An example of a die with a great aspect ratio is presented and compared with experimental results.
Keywords: Extrusion; Pocket design; Die; Finite element method; Optimisation